The Role of Non-Coding RNAs in the Sorafenib Resistance of Hepatocellular Carcinoma - Hu, Xinyao; Zhu, Hua; Shen, Yang; Zhang, Xiaoyu; He, Xiaoqin; Xu, Ximing (Frontiers in Oncology, 2021)
Hepatocellular carcinoma (HCC) is the second most common cause of cancer-related death. Sorafenib is approved by the U.S. Food and Drug Administration to be a first-line chemotherapy agent for patients with advanced HCC. A portion of advanced HCC patients can benefit from the treatment with sorafenib, but many patients ultimately develop sorafenib resistance, leading to a poor prognosis. The molecular mechanisms of sorafenib resistance are sophisticated and indefinite. Notably, non-coding RNAs (ncRNAs), which include long ncRNAs (lncRNAs), microRNAs (miRNAs) and circular RNAs (circRNAs), are critically participated in the occurrence and progression of tumors. Moreover, growing evidence has suggested that ncRNAs are crucial regulators in the development of resistance to sorafenib. Herein, we integrally and systematically summarized the molecular mechanisms and vital role of ncRNAs impact sorafenib resistance of HCC, and ultimately explored the potential clinical administrations of ncRNAs as new prognostic biomarkers and therapeutic targets for HCC.